2014
DOI: 10.1155/2014/812351
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of Neuronal Morphology: Prenatal Development of the Human Dentate Nucleus

Abstract: The aim of the study was to quantify the morphological changes of the human dentate nucleus during prenatal development using mathematical models that take into account main morphometric parameters. The camera lucida drawings of Golgi impregnated neurons taken from human fetuses of gestational ages ranging from 14 to 41 weeks were analyzed. Four morphometric parameters, the size of the neuron, the dendritic complexity, maximum dendritic density, and the position of maximum density, were obtained using the modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Because the forests analysed here are morphologically complex, showing very often fragmented and non-uniform patterns and because the particle descriptors depend on the scale of observation 48 , the forest images were further examined by fractal analysis as this is a scale-invariant method. Fractal dimension (FD) as the main fractal parameter predominantly describes the degree of morphological complexity 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Because the forests analysed here are morphologically complex, showing very often fragmented and non-uniform patterns and because the particle descriptors depend on the scale of observation 48 , the forest images were further examined by fractal analysis as this is a scale-invariant method. Fractal dimension (FD) as the main fractal parameter predominantly describes the degree of morphological complexity 49 .…”
Section: Methodsmentioning
confidence: 99%
“…By targeting specific features, primarily nuclei [21], even the studies using nonspecifically H&E-stained tissue sections [22][23][24][25][26] were in fact not analytically hypothesis-free. Although pathologists commonly use the pan-tissue H&E staining for pathologic assessment of histology specimens, it has been considered as suboptimal for fractal analysis27.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first studies, which showed the usefulness of fractal analysis in neuroscience research, dealt with the morphological aspects of glial development (27). Following this research, further studies have concluded that FD of neuron and glial cells corresponds with the increase in their morphological complexity during development and maturation (2,28).…”
Section: Application In Neuroscience Researchmentioning
confidence: 98%